2018
DOI: 10.1002/hyp.13143
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture response to rainfall on the Chinese Loess Plateau after a long‐term vegetation rehabilitation

Abstract: The Chinese Loess Plateau (CLP) is a unique Critical Zone with deep loess deposits, where soil moisture is primarily replenished by seasonal monsoon rainfall. However, the role of vegetation, coupled with complex topography, on rainwater infiltration on the CLP, especially after long‐term revegetation for controlling erosion, is inadequately quantified. Over the growing season of 2016, we monitored soil moisture at the 30‐min interval at 5 depths (10, 20, 40, 60, and 100 cm) in an afforested catchment and a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 64 publications
(98 reference statements)
4
54
5
Order By: Relevance
“…The observed differences were likely related to wetter conditions (e.g., less bypass flow due to hydrophobicity, larger hydraulic conductivity of the matrix) in the deforested part of the catchment (Figure 3) and the larger amount of direct rainfall (no interception). Whereas the results presented here showed clear differences in sequential flow occurrence, several earlier studies have reported clear differences in preferential flow occurrence that were related to different vegetation types [27,39,40,49]. Alaoui et al [27] found preferential flow both in forest and in grassland soil, but dye patterns suggested stronger interactions between macropores and matrix for forest soils.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationcontrasting
confidence: 70%
See 4 more Smart Citations
“…The observed differences were likely related to wetter conditions (e.g., less bypass flow due to hydrophobicity, larger hydraulic conductivity of the matrix) in the deforested part of the catchment (Figure 3) and the larger amount of direct rainfall (no interception). Whereas the results presented here showed clear differences in sequential flow occurrence, several earlier studies have reported clear differences in preferential flow occurrence that were related to different vegetation types [27,39,40,49]. Alaoui et al [27] found preferential flow both in forest and in grassland soil, but dye patterns suggested stronger interactions between macropores and matrix for forest soils.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationcontrasting
confidence: 70%
“…The macropores in the grassland soils, on the other hand, showed little interaction with the surroundings. Jin et al [39] and Demand et al [40] found clear differences in preferential flow occurrence between grassland and forested sites. Zhao et al [49] also observed more preferential flow occurrence for a forest site as compared to a grassland site.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationmentioning
confidence: 97%
See 3 more Smart Citations